Inhalation of Molecular Hydrogen, a Rescue Treatment for Noise-Induced Hearing Loss - Fransson, Anette Elisabeth; Videhult Pierre, Pernilla; Risling, Mårten; Laurell, Göran Frans Emanuel (Frontiers in Cellular Neuroscience, 2021)
Noise exposure is the most important external factor causing acquired hearing loss in humans, and it is strongly associated with the production of reactive oxygen species (ROS) in the cochlea. Several studies reported that the administration of various compounds with antioxidant effects can treat oxidative stress-induced hearing loss. However, traditional systemic drug administration to the human inner ear is problematic and has not been successful in a clinical setting. Thus, there is an urgent need to develop rescue treatment for patients with acute acoustic injuries. Hydrogen gas has antioxidant effects, rapid distribution, and distributes systemically after inhalation. The purpose of this study was to determine the protective efficacy of a single dose of molecular hydrogen (H2) on cochlear structures. Guinea pigs were divided into six groups and sacrificed immediately after or at 1 or 2 weeks. The animals were exposed to broadband noise for 2 h directly followed by 1-h inhalation of 2% H2 or room air. Electrophysiological hearing thresholds using frequency-specific auditory brainstem response (ABR) prior to noise exposure and before sacrifice. ABR thresholds were significantly lower in H2-treated animals at 2 weeks after exposure, with significant preservation of outer hair cells in the entire cochlea. Quantification of synaptophysin immunoreactivity revealed that H2 inhalation protected the cochlear inner hair cell ribbon synapse. The inflammatory response was greater in the stria vascularis, showing increased Iba1 due to H2 inhalation. Repeated administration of H2 inhalation may further improve the therapeutic effect. This animal model does not reproduce conditions in humans, highlighting the need for additional real-life studies in humans.